2018
DOI: 10.24042/jipfalbiruni.v7i2.2629
|View full text |Cite
|
Sign up to set email alerts
|

Inquiry-Discovery Empowering High Order Thinking Skills and Scientific Literacy on Substance Pressure Topic

Abstract: Inquiry-discovery learning plays an important role in improving high-order thinking skills (HOTS) and scientific literacy (SL). In this HOTS and SL research, it was designed with Inquiry-discovery based learning. The purpose of this study was to promote Inquiry discovery models in empowering higher-order thinking skills and scientific literacy in physics with different classes. This research used Quasi-Experimental Design research, and Pretest-Posttest Control Group Design. The research analysis design matrix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
0
12
0
6
Order By: Relevance
“…In addition, this cooperative method has been proven in previous studies that can improve significant achievements in the fields of science and other relevant fields such as (the arts, humanities, and social sciences). Cooperative learning also increases positive attitudes towards learning (Hudha & Jayanti, 2018), improve social relations (Putra, 2015), in addition to high self-esteem and cohesiveness (Untari, 2017).Cooperative learning can also be expressed in terms of learning strategies where students work together to achieve learning goals (Gillies, 2016).…”
Section: Cooperative Learning and "Map Of The Network Tree Concept"mentioning
confidence: 99%
“…In addition, this cooperative method has been proven in previous studies that can improve significant achievements in the fields of science and other relevant fields such as (the arts, humanities, and social sciences). Cooperative learning also increases positive attitudes towards learning (Hudha & Jayanti, 2018), improve social relations (Putra, 2015), in addition to high self-esteem and cohesiveness (Untari, 2017).Cooperative learning can also be expressed in terms of learning strategies where students work together to achieve learning goals (Gillies, 2016).…”
Section: Cooperative Learning and "Map Of The Network Tree Concept"mentioning
confidence: 99%
“…Initial studies at SMAN 1 Singosari showed that, during the Covid-19 Pandemic, the duration of 1 hour of lessons was only 25 minutes, students did not have the opportunity to do simple practicums, classes were divided into offline and online, and students had difficulty focusing on learning, especially in online learning. Providing lots of practice to students through the inquiry process can influence higher order thinking skills (Wartono et al, 2018), explore new media for students to have a fun learning (Leasa et al, 2016), and making students focus on learning by inquiry model (Wartono et al, 2019). Thus, this study aims to develop an inquiry-based student worksheet package assisted by traditional games on the momentum and impulse topic and to analyze the differences in inquiry achievement for students in online and offline classes.…”
Section: Introductionmentioning
confidence: 99%
“…One way to improve higher-order thinking skills is by learning scientific literacy based. The results of previous studies indicate that the increase in scientific literacy skills will be balanced with an increase in higher-order thinking skills [10]. Through science literacy-based learning, students are expected to be able to obtain new knowledge, identify problems, explain scientific phenomena, and draw conclusions [11].…”
Section: Introductionmentioning
confidence: 99%